THE MECHANISM OF FOODSTUFF PURCHASING AT SWISS BELINN SKA HOTEL PEKANBARU - Wiwiya "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Purchasing foodstuffs is a basic stage in the production proccess that determines the quality of a dish as well as the stage in product pricing. The purpose of this research is to know how is the mechanism of foodstuff purchasing at Swiss Belinn SKA Hotel Pekanbaru, the process of purchasing started from the process of requisition to the delivery process by the Supplier. This research used qualitative descriptive method to analyze the problem. The sample of this research are 3 informants which is consisting of Purchasing Supervisor, Executive Chef and Receiving Clerk. The technique of collecting data in this research are by observation and interview. Based on the research, Swiss Belinn SKA Hotel Pekanbaru used Power Pro System. The purchase is done by two ways, they are by Market list and Purchase request. Between The Hotel and Supplier does not use the contract system but by establishing good coorperation. The ordering is done by contacting the Supplier one day before production. The foodstuff will deliver by The Supplier on working hours. The foodstuff have to be checked in advance of its completeness and suitability by The Receiving Clerk and then will be stored by storekeeper.Key words : Mechanism, Purchasing, Foodstuff, Hotel